Fungos endofíticos de Serjania lethalis A.St-Hil e seu potencial fitotóxico - Abdalla, Viviane de Cassia Pereira (Universidade Federal de São Carlos, 2018)
Endophytic fungi live asymptomatically within plant organs without causing them any harm. These fungi live in symbiotic association with plants, and their secondary metabolism produces compounds that are used by plants as a defense mechanism to attack predators and pathogens. In this work, 29 endophytic fungi were isolated from healthy mature leaves of Serjania lethalis, a liana belonging to the family Sapindaceae of common occurrence in the Brazilian cerrado. These fungi were characterized macro and microscopically, and some genera could be identified with the aid of molecular biology techniques. This work was a pioneer in the isolation, and identification of endophytes in this plant species. Two fungi were selected for the studies of evaluation of the phytotoxic potential, being them an Alternaria sp, and a Diaporthe sp. For these studies two extracts of each fungus were initially prepared, a mycelial extract, and an extract of culture medium. The former was extracted with ethanol, and the second with ethyl acetate. An extract of sterile culture medium was also prepared. Initially, the extracts were tested on the growth of wheat coleoptiles (Triticum aestivum) in order to select the most active ones, and it was verified that the extract of culture medium of Alternaria sp and the mycelial extract of Diaporthe sp. were those that presented greater phytotoxicity on the growth of the coleoptilos, when compared with the negative control treatment. The extract of sterile culture medium was not active. The most active extracts from each fungus were seed germination, seedling growth, and metaxilema cell growth experiments with the invasive species Euphorbia heterophylla, and Megathyrsus maximus. The extract of Alternaria sp culture medium was found to be phytotoxic for the growth of E. heterophylla seedlings. The mycelial extract of the fungus Diaporthe sp. decreased the percentage of seed germination, and growth of the root of M. maximus seedlings. It was also phytotoxic for the growth of Euphorbia heterophylla seedlings. Such extracts contain secondary metabolites produced by the fungi that are responsible for such activities. In order to know the metabolites present in the culture medium extract of Alternaria sp. This extract was fractionated on a normal phase silica column, and its fractions were analyzed by mass spectrometry (HPLC-MS), and nuclear magnetic resonance (NMR) Thus, indol-3-carboxylic acid and the diketopiperazines cycle (Pro-Leu), cycle (Pro-Val), and cycle (Pro-Ile) were identified. These compounds were tested on growth of wheat coleoptiles and the results indicated that only indole-3- carboxylic acid (ICA) was phytotoxic for wheat coleoptile growth. The phytotoxic 8 activity of ICA was better explored by carrying out tests on seed germination, seedling growth, and metaxilema cells of Euphorbia heterophylla and Megathyrsus maximus. A buffer solution and indoleacetic acid (IAA), a plant hormone with a similar structure to ICA, were used as controls. It was verified that ICA affected the parameters of the germination of the two invasive species tested, as well as the growth of the aerial part and root of E. heterophylla, and the root of M. maximus. Controls did not affect any of the parameters studied. ICA esterification reactions were performed with three different alcohols, methanol, ethanol and hexanol, producing, respectively, the methyl esters Methyl-Indole-3-carboxylate, Ethyl-Indole-3-carboxylate, and Hexyl- Indole-3-carboxylate. The phytotoxic activity of the three esters was evaluated by growth of wheat coleoptiles, and it was found by increasing the alkyl chain, it promotes an increase in phytotoxicity. The IC50 and the lipophilicity coefficient were measured, and together they showed a lower IC50 value for the higher chain esters, and a higher lipophilicity index for them. Thus, we conclude that ICA, a secondary metabolite produced by the endophytic fungus of Serjania lethalis leaves, was phytotoxic to the invasive species tested, and it is a promising natural phytotoxic agent.
Endophytic fungi from Serjania lethalis A.St-Hil leaves and their phytotoxic potential
Keywords: Fungos endofíticos; Fitotoxicidade; Herbicidas naturais; Serjania lethalis; Phytotoxins; Esterification reactions; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA